2016
DOI: 10.3389/fnins.2016.00092
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Enrichment of Epigenetic States Around Triplet Repeats that Can Undergo Expansions

Abstract: More than 30 human genetic diseases are linked to tri-nucleotide repeat expansions. There is no known mechanism that explains repeat expansions in full, but changes in the epigenetic state of the associated locus has been implicated in the disease pathology for a growing number of examples. A comprehensive comparative analysis of the genomic features associated with diverse repeat expansions has been lacking. Here, in an effort to decipher the propensity of repeats to undergo expansion and result in a disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…Epigenetic changes have been implicated in several triplet expansion disorders (Nageshwaran and Festenstein, 2015). It has also been suggested that the repeats that undergo expansion have a distinct association with epigenetic features (Essebier et al, 2016). Our findings reinforce the importance of epigenetic changes in establishing the disease state caused by triplet repeat expansions.…”
Section: Sirna-mediated Epigenetic Silencing Underlies the Triplet Expansion-associated Transcriptional Downregulation Of The Affected Gesupporting
confidence: 82%
“…Epigenetic changes have been implicated in several triplet expansion disorders (Nageshwaran and Festenstein, 2015). It has also been suggested that the repeats that undergo expansion have a distinct association with epigenetic features (Essebier et al, 2016). Our findings reinforce the importance of epigenetic changes in establishing the disease state caused by triplet repeat expansions.…”
Section: Sirna-mediated Epigenetic Silencing Underlies the Triplet Expansion-associated Transcriptional Downregulation Of The Affected Gesupporting
confidence: 82%
“…This characteristic, which is stable across different cell types during early human development, was shown to be disrupted in the FMR1 gene in Fragile X syndrome patients, which correlated with the silencing of that gene. Another study had revealed the absence of repressive marks in CAG expansions related genes ( 20 ). We also provide exemplar density plots for the HM in their genomic coordinates for the polyQ disease-related gene ATXN7 and for another long polyQ-containing gene, which is not disease-associated, FOXP2 ( Supplementary Figure S5 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, less is known about the causes for repeat expansions that take place in genes that encode for proteins with repeat tracts within the normal range. In healthy cells, DNA methylation and active histone marks were suggested to be enriched around disease-associated TNRs ( 20 ). Interestingly, CAG repeat expansions in bacterial and yeast models, as well as in vitro models using human cell extracts, demonstrated that even short, normal range, repeat tracts are unstable, with a tendency to expand ( 21–23 ).…”
Section: Introductionmentioning
confidence: 99%